Sosialisasi Penerapan NIK Menjadi NPWP Sebagai Single Identity Number Bagi Warga RT/RW. 06/00 Kelurahan Tanjung Seneng Bandar Lampung - Rasty Yulia; Heny Herawati; Hertya Andriani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Indonesia continues to move forward in responding to the demands of the times, especially in terms of administrative modernization. One important step in this effort is updating and integrating population data with the national taxation system. In this context, Tanjung Seneng Subdistrict, Bandar Lampung, started an important initiative aimed at assisting residents in the RT/RW environment. 06/00 in the process of modernizing their Population Identification Number (NIK) into a Taxpayer Identification Number (NPWP). Modernizing NIK to NPWP is not just an administrative step, but an effort to increase tax awareness, administrative efficiency, and community involvement in national development. By involving the local community, it is hoped that this socialization will not only be a process but also an opportunity to empower residents to understand their role in economic development and shared prosperity. Several problems that arise, namely: The level of public understanding regarding NIK modernization, Citizens’ understanding regarding NPWP and its relationship to NIK, and The impact of NIK modernization on administrative processes. By providing socialization on the modernization of NIK into NPWP for RT/RW residents: 06/00 residents will not need to carry NPWP cards and will only need to bring KTPs, making tax administration easier by using a single identity, increasing efficiency and effectiveness.